Potential risks of microplastics and global warming factors on early growth and development of the sea urchin (Paracentrotus lividus). - Bertucci, Juan Ignacio; Bellas, Juan (2021)
The aim of this work was to estimate the risk of the combined effect of global warming factors and microplastic (MP) pollution on the development of the sea urchin P. lividus. Embryo-larval bioassays were conducted to determine growth and morphology after 48 h of incubation with MP (1000 and 3000 particles/mL); with filtered sea water at pH = 7.6; and with their combinations. A second experiment was conducted to study the effect of pH and MP in combination with a temperature increase of 4 °C compared to control (20 °C). We found that the inhibition of growth in embryos reared at pH = 7.6 was 75 %. Larvae incubated at 3000 MP particles/mL showed a 20 % decrease in growth compared to controls. The exposure to MPs also induced an increase in the postoral arm separation or rounded vertices. The combined exposure to a pH 7.6 and MPs caused a significant decrease of larval growth compared to control and to pH 7.6 treatments. Morphological alterations were observed in these treatments, including the development of only two arms. Increasing the temperature from 20 °C to 24 °C resulted in an increase of growth that was also observed in the pH 7.6 and pH 7.6 + MP3000 treatments, but the relative stomach volume decreased. In this work we demonstrated that MP could aggravate the effect of a decreased pH and increased temperature in P. lividus larvae, causing a lower growth and an altered development. Therefore, the combined stress caused by ocean warming and acidification, and microplastic pollution, could threaten sea urchin populations leading to an impact on coastal ecosystems.